(untitled) ("Journal "U". Economy. Management. Finance.", 2026)
The article is devoted to the study of the impact of digital technologies (Fintech) on the transformation of banking services, especially in the field of lending and risk management. The changes that occur due to the introduction of innovations are considered, such as improving the efficiency of credit processes, improving risk analysis, and enhancing transaction security. Special attention is paid to the advantages and challenges of digital transformation of banks and the formation of new approaches to interaction between banks and customers.